Pengaruh Perputaran Modal Kerja dan Perputaran Kas Terhadap Profitabilitas - Seto Sulaksono Adi Wibowo; Merlin Merlin; Yosi Handayani (Journal of Applied Accounting and Taxation, 2021)
The objective this study are to determine the effect of working capital and the cash turnover on the level of profitability in insurance companies. Working capital variable is measured by working capital turnover (X1), the effectiveness of the use of cash is measured by cash turnover (X2) and profitability is measured by return on investment/ROI (Y). The population in this study is an Insurance Company listed on the Indonesia Stock Exchange from 2011-2015. The sample in this study is taken by using purposive sampling technic. Samples consist are 50 financial statements that meet the criteria. The type of data used in this study is secondary data originating and published from the Indonesia Stock Exchange. The collected panel data then analyzed by using model test, classical assumption, multiple regression analysis, t test, and determinant coefficient analysis to see the level of conformity of the analysis. The result of this research shows that the rotation of working capital has a positive effect on profitability, it can be seen from t value> t table (2.181> 2.010) and cash turnover has no significant effect on profitability, can be seen from t value <t table (-1,771 < 2.010).